以相當於權利金數額為專利侵害損害額―日本特許法第102條第3項之研究 The Research of Japanese Patent Law Article 102(3) - 王銘勇 Ming-Yung Wang (Kējì Fǎxué Pínglùn, 2010)
經濟部智慧財產局2009 年5 月公布之專利法修正案第85 條第1 項第3款增訂與日本特許法第102 條第3 項相類似之規定，以權利金相當數額為侵害專利權損害賠償計算損害方法之一，本文茲就日本特許法關於侵害專利之損害賠償規範架構加以說明，並分析日本特許法第102 條第3 項之性質。本文分析後發現日本司法實務就特許法第102 條第3 項所定之權利金相當數額之判斷上，係考量授權契約、業界市價、發明專利之內容、有無可替代性、該發明專利之貢獻度、侵害商品販賣之價格、數量、期間、相關人之態度、侵害者之努力及在市場上當事人之地位等因素，且日本司法實務認特許法第102 條第3 項權利金相當數額不等於其他授權契約之權利金、決定相當權利金數額時係考量前揭相關因素、有增減之原因時增加或減少之比例數不明確，此均可為我國爾後立法及司法實務執法之參考。 A patentee or an exclusive licensee may claim against an infringer compensation for damage sustained as a result of the intentional or negligent infringement of the patent right or exclusive license, by regarding the amount the patentee or exclusive licensee would have been entitled to receive for the working of the patented invention as the amount of damage sustained, by applying Japanese Patent Law Article 102(3). This report is to discuss the problems of Japanese Patent Law Article 102(3). Japanese courts have granted damages in the form of a reasonable royalty in most of all cases. The royalty is defined as the amount that a patentee ordinarily receives as compensation for allowing exploitation of the patented invention. This paper concludes that the amount of money commensurate to the patentee’s loyalty is not always awarded equally to the amount of money objectively commensurate to the patentee’s loyalty, on the basis of the amount of average loyalty in the same profession, the amount of loyalty intended for national patents, and so on. The amount of money commensurate to the patentee’s loyalty may be awarded on the basis of the value of the patented invention and various circumstances surrounding parties concerned. These various circumstances include business relationship between the parties concerned, the amount of profit that the infringer actually gained by infringement, for example.